Doomed Youth: Antonio Cánovas, a Young Sportsman in Time of War in 1930s Spain - Viuda-Serrano, Alejandro; Ibarrondo-Merino, Iker (Frontiers in Sports and Active Living, 2021)
During the Spanish Civil War (SCW) 1936–1939, many young working-class sportsmen volunteered. They were both physically and politically active and some of them outstanding athletes. The search of these unknown men has just begun. Doomed Youth is a tribute to them and the first step toward a bigger attempt to better comprehend the role of sportsmen volunteers enlisted during the first months of the SCW, a fact that to date has received little scholar attention. Archival research, especially war combatants' family records as well as newspaper archives, oral memories of the protagonists left alive, and historical contextualization were defined as the appropriate methods to conduct the research. This paper is devoted to one of these young volunteers, Antonio Cánovas, recently dead in 2018 at the age of 98, whose life story in the 1930s and 1940s may be taken as the epitome of the young working-class sportsman of the cutting-edge regions of Spain in the first half of the 20th century: youngsters aware of their political and social rights whose dreams of social justice and active life were dashed by the war.